2005
DOI: 10.1007/bf02985047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hemodynamics of the femoral head compared with the ilium, femoral neck and femoral intertrochanteric region in healthy adults: Measurement with positron emission tomography (PET)

Abstract: The present study demonstrated that the femoral head is in a hypoemic state as compared with other osseous tissue, indicating that even the slightest exacerbation of hemodynamics in the femoral head can trigger an ischemic condition culminating in ONF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…2 Nakamura et al evaluated the hemodynamics of the femoral head by using PET and concluded that the femoral head is in an ischemic state compared with the ilium, femoral neck, and intertrochanteric regions. 3 In conclusion, we believe that this method for measuring intramedullary oxygen tension is simpler and less invasive than other currently used methods and has the possibility for intraoperatively identifying a risk group that can develop a late segmental collapse of the femoral head secondary to avasucular necrosis. …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…2 Nakamura et al evaluated the hemodynamics of the femoral head by using PET and concluded that the femoral head is in an ischemic state compared with the ilium, femoral neck, and intertrochanteric regions. 3 In conclusion, we believe that this method for measuring intramedullary oxygen tension is simpler and less invasive than other currently used methods and has the possibility for intraoperatively identifying a risk group that can develop a late segmental collapse of the femoral head secondary to avasucular necrosis. …”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4] Hirata et al reported that dynamic MRI was useful for prediction of union after femoral neck fracture. 1 Sugamoto et al reported that the laser Doppler device was useful to measure hemodynamics in the femoral neck fractures and Garden stage III fractures should be subdivided into 2 groups according to their hemodynamics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Haemodynamic studies using positron emission tomography have shown that the femoral head is always in a hypovolaemic state compared with other osseous tissue. 34 Both the extra-and the intraosseous blood supplies of the femoral head are susceptible to injury in patients with a femoral neck fracture. Although the major intraosseous vessels are nearly always damaged, injury to the extraosseous vessels is proportional to the amount of displacement of the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic activity in sites of osteonecrosis has been detected during 18 F-FDG PET or PET/CT performed for disease staging; these sites of osteonecrosis may mimic metastatic lesions [56]. Preliminary investigations in adults have found FDG PET to be a sensitive imaging method for detecting osteonecrosis [57][58][59] and in assessing perfusion of the femoral head [57,58]. However, prospective reports in pediatric cases are lacking.…”
Section: Functional Imagingmentioning
confidence: 99%